2018
DOI: 10.3390/en11113120
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Current of Multi-Needle Negative Corona Discharge and Its Electromagnetic Radiation Characteristics

Abstract: Negative corona discharge occurs widely in high voltage transmission lines and other “high voltage” uses, which can cause strong electromagnetic interference (EMI). In this research, the pulse current of multi-needle negative corona discharge and its electromagnetic (EM) radiation characteristics were studied and compared with that of single-needle negative corona discharge. A dipole radiation model was established to analyze the EM radiation characteristics of the negative corona discharge. The results show t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
(38 reference statements)
1
5
0
Order By: Relevance
“…Qualitative features of positive and negative corona are very similar to those observed in other studies (i.e. Kexin et al, 2015;Wang et al, 2017;Moreau et al, 2018;Wang et al, 2018). For the same applied voltage, positive corona pulses have higher amplitudes and lower frequency in comparison to negative corona pulses.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Qualitative features of positive and negative corona are very similar to those observed in other studies (i.e. Kexin et al, 2015;Wang et al, 2017;Moreau et al, 2018;Wang et al, 2018). For the same applied voltage, positive corona pulses have higher amplitudes and lower frequency in comparison to negative corona pulses.…”
Section: Discussionsupporting
confidence: 85%
“…The shunt resistor affects significantly the shape of the waveform, since current pulses are very fast, with a rise time of tens of nanoseconds and decay of a few hundreds of nanoseconds (e.g. Kexin et al, 2015;Wang et al, 2017;Dordizadeh et al, 2017;Wang et al, 2018). If higher values of resistors are used, current pulses have a longer duration.…”
Section: Methodology and Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…The electric field in the plasma region cannot provide sufficient energy for the electrons. Therefore, the electrons combine with the neutral air molecules to form negative ions in the plasma region, then enter the drift region, and move towards the ground electrode 36 . In other words, in corona discharge, negative ions are emitted from the needle electrode and are incident to the SEL film owing to the potential difference between the needle electrode and the ground (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Corona discharge has been studied for many years because of its potential applications. The corona discharge in point-plane electrode geometry has been used as a negative ion source in electrical appliances, and in mass and ion mobility spectrometers [3]. Later it was empirically found that the Townsend relation could also be used approximately for point-toplane geometry, as Henson disclosed [4].…”
Section: Introductionmentioning
confidence: 99%